PENERAPAN MEDIA GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SIWA SMA - Lestari Roswahyuliani; Tina Rosyana; Wahyu Setiawan; Gida Kadarisma (IKIP Siliwangi, 2022)
Learning mathematics using the concept of mathematical understanding is needed to solve a mathematical problem. This research is a classroom action research (CAR) which aims to analyze the ability to understand students’ mathematical concepts in SPtLDV material with the help of geogebra media. The subjects of this study were 20 students of class X Senior High School 1 Cisarua with low, medium, and high categories. The instruments used are the initial tests (before the action); the first and second cycle test (after giving the action); interview; observation sheets for teachers and students regarding the research conducted. The resultas obtained in the pre-cycle are 30%, in the first cycle there are 45%, and in the second cycle there are 90% who have the ability to understand students’ understanding of the SPtLDV material. Based on the research that has been done, it can be concluded that the students’ mathematical understanding ability on SPtLDV material assisted by geogebra media has increased.